Evaluación de los efectos de la aplicación de tres concentraciones de CO2 bajo invernadero en el cultivo de lechuga crespa (Lactuca Sativa Vas. Crispa), en el sector Salache, cantón Latacunga, provincia Cotopaxi. - Hurtado Salazar, Cristian Andrés (2023)
The present investigation had as main purpose "The evaluation of the effects of the application of three concentrations of CO2 under a greenhouse", where it was determined which of the concentrations studied presents a greater development in the Cultivation of Crispy Lettuce (Lactuca sativa vas. Crispa) , for which it was used an experimental design of completely randomized blocks was taken in AXB+1 factorial arrangement with three treatments and three repetitions, later the application of CO2 concentrations in the crop was carried out, which were applied in doses of 650 ppm, 850 ppm and 1000 ppm in a time of 4 hours in the same way doses of 650 ppm, 850 ppm and 1000 ppm were applied in a time of 6 hours and a control which did not apply any concentration of CO2 to which the same was given temperature and humidity conditions under greenhouse to continue with the data tabulation, data collection was carried out every 15 days. The stable dose of CO2 for the Plant Height Variable was C1T1 (650 ppm, 4 hours of exposure) with an average height of 10.34 cm, in the leaf number the dose that this May determines was the C1T1 dose (650 ppm, 4 hours of exposure) with a mean of 13.42, with C2T1 (850 ppm of CO2, 4 hours of exposure) being the second with the highest determination in the evaluated variables.